2019
DOI: 10.1080/21691401.2018.1548468
|View full text |Cite
|
Sign up to set email alerts
|

Folate-conjugated human serum albumin-encapsulated resveratrol nanoparticles: preparation, characterization, bioavailability and targeting of liver tumors

Abstract: This work investigated the preparation of specific targeted drug delivery systems in cancer chemotherapy by folate conjugated human serum albumin nanoparticles encapsulated resveratrol (RES) nanoparticles (FA-HSA-RESNPs). FA was coupled to HSA, and RES was encapsulated in FA-conjugated HSA by high pressure fluid nano-homogeneous emulsification. The average particle size and polydispersity index of NPs prepared under optimal conditions were 102.1 ± 4.9 nm and 0.001. The drug capsulation efficiency and drug load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…In addition, bioavailability of RSV-loaded HSA-FA nanoparticles turned out to be six times higher than the free polyphenol and no toxic effects of RSV-loaded HSA-FA nanoparticles were detected on healthy rat organs. In contrast, the decrease in size of the tumor was not mentioned [63].…”
Section: Seeking Innovative Formulations Of Resveratrolmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, bioavailability of RSV-loaded HSA-FA nanoparticles turned out to be six times higher than the free polyphenol and no toxic effects of RSV-loaded HSA-FA nanoparticles were detected on healthy rat organs. In contrast, the decrease in size of the tumor was not mentioned [63].…”
Section: Seeking Innovative Formulations Of Resveratrolmentioning
confidence: 94%
“…The incorporation of a cancer-targeting ligand directly into nanoparticle structures is another way to promote drug release more selectively to cancer cells. Thereby, nanoparticles have been obtained by coupling human serum albumin (HSA), a non-toxic carrier of weakly soluble drugs and folic acid (FA) a cancer-targeting ligand [63]. Antitumoral activities of RSV-loaded HSA-FA nanoparticles were evaluated in in vitro assays of human liver cancer HepG2 cells and in in vivo experiments on H22 tumor-bearing mice.…”
Section: Seeking Innovative Formulations Of Resveratrolmentioning
confidence: 99%
“…Multiple studies have shown that resveratrol encapsulated in diverse nanoparticles provides the protection for resveratrol against UV light via improving bioavailability in different targets (Summerlin et al, 2015 ). Furthermore, resveratrol-loaded liposomes have shown to be effective anti-proliferative agents in brain cancer cells such as U-87 MG cells through inhibiting cell growth and inducing apoptosis in nude mice (Teskač and Kristl, 2010 ; Duarte et al, 2015 ; Summerlin et al, 2015 ; Jhaveri et al, 2018 ; Latruffe and Vervandier-Fasseur, 2018 ; Lian et al, 2019 ). In addition, the combination of resveratrol and 5-fluorouracil- (5-FU) loaded ultradeformable liposomes in an ex vivo study showed the ability to penetrate and deposit in the deep porcine skin layer.…”
Section: Resveratrol As a Nanodrugmentioning
confidence: 99%
“…Although the utilization of organic solvents to prepare NPs is preferred, many materials are di cult to dissolve in both water and organic solvent. One way to prepare such NPs without applying organic solvents is to use ethanol [23].…”
Section: Characterization Of Fa-has-dox Npsmentioning
confidence: 99%